Romper estereotipos de género en la identidad profesional docente: una propuesta de paz - Pinzón Varilla, Luisa (Educación y Ciudad, 2016)
The aim of this paper is to present a preview of the results of the doctoral research : “Narratives of teacher professional identity in gender perspective”. This research focused on understanding the profesional identities of the teachers of the Capital District of Bogota (Colombia). The study analyzed and interpreted a corpus of biographical narratives about experiences of gender that are experienced in the exercise of the teaching profession. Methodologically, the qualitative research approach was adopted hermeneutic.